Public Awareness About Sepsis in Türkiye: A Survey Study - Cüneyt Kurum; Ali İşçanan; Aslıhan Alioğlu; Zeliha Sena Karataş; Youssef Alothman; Kerem Ülker; Şeyma Nur Dik; Abdullah Palabıyık; Züleyha Aydın; İlker İnanç Balkan (Cerrahpaşa Medical Journal)
Objective: Sepsis is a severe medical condition characterized by life-threatening organ dysfunction due to an imbalanced immune response to infection. Delayed diagnosis often leads to high mortality rates, with approximately 50 million cases and 11 million deaths globally each year. Despite its significant impact on health and economics, public awareness of sepsis is low, especially among non-healthcare professionals. This study, conducted by fifth-year students from İstanbul University-Cerrahpaşa, Cerrahpaşa Faculty of Medicine, aims to evaluate and enhance sepsis awareness among diverse segments of the Turkish population.